Dynamic measurement of particle diameter and drag coefficient using the ultrasonic method - SOMMERLATT, Hans Dieter; ANDRUSZKIEWICZ, Artur (Archives of Acoustics, 2008)
The possibility of ultrasonic impulse echo method utilization for diameter determination in liquids and for frontal drag coefficient calculation has been presented in this paper. The investigations were carried out in uniform and accelerated motion area for steel and glass balls freely falling in a water-filled tank. The accuracy of this method as a function of flight time readout resolution and ultrasonic wave velocity equation, assumed for calculations has been analyzed as well. Its further utilization in two-phase liquid metal/gas flow investigations has been proposed in this paper.